Naive infection predicts reservoir diversity and is a formidable hurdle to HIV eradication - Marilia R. Pinzone; Sam Weissman; Alexander O. Pasternak; Ryan Zurakowski; Stephen Migueles; Una O’Doherty (JCI Insight, 2021)
Historically, naive cells have been considered inconsequential to HIV persistence. Here, we compared the contributions of naive and memory cells to the reservoirs of individuals with a spectrum of reservoir sizes and variable immunological control. We performed proviral sequencing of approximately 6000 proviruses from cellular subsets of 5 elite controllers (ECs) off antiretroviral therapy (ART) and 5 chronic progressors (CPs) on ART. The levels of naive infection were barely detectable in ECs and approximately 300-fold lower compared with those in CPs. Moreover, the ratio of infected naive to memory cells was significantly lower in ECs. Overall, the naive infection level increased as reservoir size increased, such that naive cells were a major contributor to the intact reservoir of CPs, whose reservoirs were generally very diverse. In contrast, the reservoirs of ECs were dominated by proviral clones. Critically, the fraction of proviral clones increased with cell differentiation, with naive infection predicting reservoir diversity. Longitudinal sequencing revealed that the reservoir of ECs was less dynamic compared with that of CPs. Naive cells play a critical role in HIV persistence. Their infection level predicts reservoir size and diversity. Moreover, the diminishing diversity of the reservoir as cellular subsets mature suggests that naive T cells repopulate the memory compartment and that direct infection of naive T cells occurs in vivo.